Phubbing and Social Relationships: Results from an Australian Sample. (18th June 2019) - Al-Saggaf, Yeslam; MacCulloch, Rachel
Abstract: Existing research on phubbing has focused mainly on one relationship group (i.e., partner phubbing). How does phubbing differ across different relationship groups (i.e., family vss people at work)? How does phubbing differ within the same relationship group (i.e., in the case of family relations: parents vs. children)? In which situations (i.e., in bed or at the dinner table) are people more likely to phub others? An online survey of 387 participants, predominantly Australians, revealed that participants were more likely to phub family, friends and strangers than people at work, and they were more likely to phub family and friends than strangers. With regard to family relations, participants were more likely to phub parents, partners and children than grandparents. They were more likely to phub partners and children than parents. The reason certain people are phubbed more frequently than others and in specific situations more than others is due to which social norms matter the most: injunctive norms or smartphone-related internalised norms. Considering that phubbing impacts those with whom the phubber has a closer relationship and those with whom the phubber has a distant relationship, comparing how phubbing differs across different relationship groups contributes to understanding the impact of phubbing on social relationships.